2022
DOI: 10.5296/jas.v9i2.18032
|View full text |Cite
|
Sign up to set email alerts
|

Economic Viability Analysis of an Oral Anthelmintic Treatment for Cattle in Feedlot

Abstract: The economic viability of a commercial oral anthelmintic suspension containing 10% fenbendazole was evaluated in Angus x Nelore cattle in a feedlot. Two groups of 37 animals (treated and non-treated) were formed. A random-block design was used based on initial weight, egg count per gram of feces (EPG) and carcass grade. EPG counts and the determination of weight were performed on Days 0, 42 and 122. Carcass grade and yield were determined on the day of slaughter. Economic viability was evaluated using cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Production and financial gain following nematode treatment have been demonstrated for all sectors of beef cattle production, in temperate, subtropical and tropical climates [7,13,17,22,24,43,67,85,86,99,145,[148][149][150][151][152][153][154]. For example, results from a meta-analysis of over 170 research trials utilizing 20,000 MonteCarlo simulations to evaluate the impact of various pharmaceutical technologies on the cost of cattle production revealed that elimination of deworming resulted in increased cattle production cost of US$190 per head over the lifetime of the animal, based on 2005 US production costs and sale prices [24].…”
Section: Nematodes-major Species Health Impact and Economics Of Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…Production and financial gain following nematode treatment have been demonstrated for all sectors of beef cattle production, in temperate, subtropical and tropical climates [7,13,17,22,24,43,67,85,86,99,145,[148][149][150][151][152][153][154]. For example, results from a meta-analysis of over 170 research trials utilizing 20,000 MonteCarlo simulations to evaluate the impact of various pharmaceutical technologies on the cost of cattle production revealed that elimination of deworming resulted in increased cattle production cost of US$190 per head over the lifetime of the animal, based on 2005 US production costs and sale prices [24].…”
Section: Nematodes-major Species Health Impact and Economics Of Controlmentioning
confidence: 99%
“…In Brazilian grazed cattle, Conde et al found that each US$1 spent on deworming, including product and labor costs, resulted in a return of US$157 and US$134 using two or three annual doses of anthelmintic, respectively [155]. Nakatani et al found that GIN treatment of Brazilian feedlot cattle with fenbendazole resulted in a net return of US$14.60 per animal [154]. The benefit of GIN treatment remained viable when modeled under optimistic, probable and pessimistic financial scenarios relative to cattle pricing [152][153][154][155].…”
Section: Nematodes-major Species Health Impact and Economics Of Controlmentioning
confidence: 99%
See 3 more Smart Citations